EXPERIENCES WITH MANAGEMENT PERINATAL INFORMATION SYSTEM HOSPITAL MARIA AUXILIADORA - Távara Orosco, Luis (2015)
The efforts of the health sector should be aimed at increasing the coverage and improve the quality of care, which must be based on good organization of services. At the same time, the organization must have an adequate system of information, which should have as support an appropriate history and a fast flow of information.